2015
DOI: 10.21512/comtech.v6i1.2296
|View full text |Cite
|
Sign up to set email alerts
|

Aplikasi Pencarian Tempat Wisata Berbasiskan GPS dengan Metode Radius dan Rating

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
2
0
3
Order By: Relevance
“…Semuel (2007) examined the influence of the media (in this case the tourism information syst e m) on market behavior. In addition, studies on the tourism creative industry are still dominant in technical matters (Kuncoro, 2014;Yulianto and Layona, 2015). Therefore, it can be concluded that studies on the tourism b usiness development process and the dynamics of maintaining business are important to be explored contextually.…”
Section: Contribution Of the Development Of Regional Creative Industrmentioning
confidence: 99%
“…Semuel (2007) examined the influence of the media (in this case the tourism information syst e m) on market behavior. In addition, studies on the tourism creative industry are still dominant in technical matters (Kuncoro, 2014;Yulianto and Layona, 2015). Therefore, it can be concluded that studies on the tourism b usiness development process and the dynamics of maintaining business are important to be explored contextually.…”
Section: Contribution Of the Development Of Regional Creative Industrmentioning
confidence: 99%
“…Rute ditampilkan dalam bentuk peta 2D dan Informasi mall yang disediakan adalah acara yang ada di setiap mall informasi serta mencakup tentang diskon atau promosi yang diadakan disetiap mall. Penelitian untuk pencarian lokasi rumah makan dikembangkan oleh Yulianto and Layona (2016), metode perancangan sistem mempergunakan UML dimana terdiri atas Use Cases Diagram, State Diagram, Sequence Diagram, serta Class Diagram sesudahnya dipergunakan guna mengolah perancangan database memakai ERD. Hasil yang digapai berbentuk suatu aplikasi pencarian rumah makan dengan nama Nomnomfood, memakai GPS di piranti mobile android yang mampu memberikan kemudahan untuk pemakai android guna menentukan tempat makan yang diharapkan serta suatu website untuk pemilik rumah makan memasukkan tempat makanya kedalam database.…”
Section: Pendahuluanunclassified
“…For example, Edwards (2013) added transport information that could be used in the system, and Shimizu (2014) added passing towards a location. The other researchers develop a nearest location searching system based on the radius (Yulianto, 2015), rating and comment (Layona, 2016a), and based on the user's desired criteria (Layona, 2016b). Their research is for the development of application aiming to track the user's position in the community (friends, colleagues, or families) with location tagging and comment which resemble a wall-post social media.…”
Section: Figure 1 Gps Systemmentioning
confidence: 99%